The Belgian business-to-business transactions dataset 2002-2021 - Emmanuel Dhyne; Cédric Duprez; Toshiaki Komatsu (National Bank of Belgium, 2023)
This paper provides an updated overview of the network of Belgian business-to-business transactions from 2002 to 2021, building on the previous vintage of the dataset which covered 2002-2014. Leveraging data from VAT client lists, we establish a comprehensive and cohesive database detailing the values of transactions between non-financial corporations in Belgium. This database encompasses all sectors, ranging from primary industries, manufacturing and utilities to construction, business services and other services. With its unmatched breadth at the level of individual firms and panel dimensionality, the dataset facilitates diverse research inquiries in areas such as industrial organisation, international trade, and network theory. To give readers a clearer picture, this paper also highlights several key insights about the Belgian network. Due to the confidential nature of the data, access to this dataset is restricted to NBB staff members.
Keywords: C67; C81; L23; 330; Firm-Level Analysis; networks; VAT transactions; firm-to-firm linkages